Implementation of the Imtaq Program in Forming the Morals of Students of Mts At-Taufiqiyyah Bluto in 2024 - Mirnawati; Achmad Maulidi (al-Afkar, Journal For Islamic Studies, 2026)
The condition of teenagers in Indonesia is currently experiencing a decline in moral character, and today’s teenagers are no longer seen as good role models in social, moral, and academic environments. Therefore, this study aims to analyze the implementation of the IMTAQ program in efforts to shape akhlakul karimah among students at MTs At-Taufiqiyyah. It also seeks to analyze how the IMTAQ program is applied in students' daily lives and to evaluate the extent to which this program plays a role in shaping students' character, particularly in terms of akhlak in accordance with Islamic teachings.The problem addressed in this research is how the IMTAQ program is implemented in shaping the students' akhlakul karimah. The research method used is a qualitative approach with a case study type, where data is collected through interviews, observations, and documentation. The research findings show that the implementation of the IMTAQ program at MTs At-Taufiqiyyah has been successful in shaping the students' akhlakul karimah. Through worship activities such as congregational prayers, tahajjud, dhuha, religious sermons, and istighosah, students undergo positive behavioral habituation, which increases their discipline, responsibility, and awareness of the importance of good morals. This program has proven to be effective in deepening the students’ understanding of Islamic teachings and encourages them to apply these values in their daily lives.